O impacto de novas tecnologias educacionais estudos sobre plataforma educacional - Oliveira, Bruno Simões Garcia de (2023)
During a pandemic moment in 2020 when people were forced to stay at home by government order and classes had to be taught online, this research sought to understand and analyze whether the generation, called “digital natives”, can exercise autonomy, so advocated and defended as one of the objectives of education. This work sought to find out whether the digital skills of young people were able to guarantee success in the teaching-learning process through the system of virtual classes and materials made available on a digital platform. Through the application of questionnaires to students in the 8th year of elementary school it can be concluded that the simple transposition of face-to-face teaching to virtual does not guarantee the development of autonomous competence, since this comprises the mediation of the teacher and it is built over time in a process of collaboration and trust between professors and students. For this reason, it is concluded that the students were unable to explore all the tools made available by the platform in question, especially those that contributed to the construction of autonomy such as access to a teacher on duty to resolve doubts and those that presented an overview of the evaluation of the student so that he could, through critical reflection, carry out a self-assessment exercise of his learning